2018
DOI: 10.1089/ten.tea.2017.0103
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Three-Dimensional Cellular Network Construction ReplicatesEx Vivothe Phenotype of Primary Human Osteocytes

Abstract: Osteocytes are deeply embedded in the mineralized matrix of bone and are nonproliferative, making them a challenge to isolate and maintain using traditional in vitro culture methods without sacrificing their inimitable phenotype. We studied the synergistic effects of two microenvironmental factors that are vital in retaining, ex vivo, the phenotype of primary human osteocytes: hypoxia and three-dimensional (3D) cellular network. To recapitulate the lacunocanalicular structure of bone tissue, we assembled and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 45 publications
2
33
0
Order By: Relevance
“…researchers developed 3D osteocyte culture models to improve upon the limitations of 2D cultures. [27][28][29][30][31][32][33] For example, one study achieved mature osteocyte differentiation in a 3D collagen gel but this culture system lacked mechanical cues. [34] Other studies revealed new effects of direct matrix strains on osteocytes in 3D [27,29,35] such as strain-induced osteocyte regulation of osteoblast bone formation.…”
Section: Doi: 101002/adhm202001226mentioning
confidence: 99%
See 1 more Smart Citation
“…researchers developed 3D osteocyte culture models to improve upon the limitations of 2D cultures. [27][28][29][30][31][32][33] For example, one study achieved mature osteocyte differentiation in a 3D collagen gel but this culture system lacked mechanical cues. [34] Other studies revealed new effects of direct matrix strains on osteocytes in 3D [27,29,35] such as strain-induced osteocyte regulation of osteoblast bone formation.…”
Section: Doi: 101002/adhm202001226mentioning
confidence: 99%
“…[27] These prior studies applied matrix strains ranging from 0.4-10%, which exceed physiological levels of strain in bone. Other studies incorporated fluid perfusion into 3D cultures [15,28,30,32,36,37] and revealed, for example, the link between fluid-induced shear and gene expression of proteins that regulate osteoblast bone formation (e.g., sclerostin). [28] However, 3D models that adequately capture both physiologically relevant matrix strains and fluid perfusion are limited.…”
Section: Doi: 101002/adhm202001226mentioning
confidence: 99%
“…1) by culturing primary human osteocytes with BCP microbeads for 14 days. Comparisons of dendrite length and cell-cell distance (Table 1) 40 between hypoxic and normoxic (from our previous studies 38 ) 3D bone tissues revealed that hypoxia induces profound changes in the 3D structure of osteocytic cells by producing cells with prolonged dendrites.
Figure 1Microfluidic perfusion device for engineering 3D bone tissues. ( a ) Actual device, containing bone tissue constructs in the central chamber with medium flowing into one inlet fed by a syringe pump and exiting through two outlets carrying effluent to a collection vial.
…”
Section: Resultsmentioning
confidence: 94%
“…In the tissue without PCa cells (−PCa cells, Fig. 2a), the osteocytes were well spread out, with dendrites protruding to neighboring cells (inset) and the endosteal layer (characterized previously 38 ) was intact (Fig. 1a, black arrows).
Figure 2Histology sections of the engineered 3D bone tissues.
…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation